PENERAPAN PERJANJIAN KERJA ANTARA DIREKTUR DAN KARYAWAN TERKAIT DENGAN ASAS KEBEBASAN BERKONTRAK BERDASARKAN PASAL 1320 KITAB UNDANG-UNDANG HUKUM PERDATA - Dina Haryati Sukardi; Dian Herlambang (PRANATA HUKUM, 2020)
The principle of freedom of contract is a principle that gives freedom to the parties to: (1) make or not make an agreement; (2) entering into agreements with anyone; (3) determine the contents of the agreement, implementation, and terms; and (4) determine the form of an agreement that is written or oral. The purpose of this study is to find out whether the work agreement between directors and employees at the Hospital of Menggala based on the principle of freedom of contract is in accordance with Article 1320 of the Civil Code, knowing the inhibiting factors in the implementation of the principle of freedom contracting to an employment agreement at the District Hospital ofalaala, and the efforts made in overcoming any obstacles that occur in the implementation of the principle of freedom of contracting with an employment contract at the District Hospital.The results of the analysis carried out that the work agreement of the Cooperative Hospital meets the principle of freedom of contract. The principle of freedom of contract is a principle that gives freedom to the parties to make or not make an agreement, enter into an agreement with anyone, determine the contents of the agreement, its implementation, requirements, determine the form of the agreement, written or oral, in making the work agreement of both the Directors and workers there is no influence or pressure from the other party, both parties give freedom to the other party to express their opinions or proposals regarding the agreement material, then the work agreement of the Shepala Regional Hospital is in accordance with the principle of freedom of contract as contained in Article 1320 of the Civil Code. In carrying out the principle of freedom of contract beer to work agreements the Cooperative Hospital experienced obstacles. Constraints faced include: (1) the absence of trade unions in fighting for workers' rights (2) Low Worker Resources. The efforts of the Penggala District Hospital in facing obstacles in implementing the principle of freedom of contract to work agreements are immediately possible to form trade unions that can bridge workers and hospital directors and hold various trainings to improve the professionalism and abilities of their employees.